The Effect Of Capital Expenditure, Local Government Revenue And Balanced Funds On Regional Income Per Capita With Number Of Population As A Moderating Variable In The Region Of North Sumatera, East Kalimantan And East Java Province - Agus Christian Hutagalung; Iskandar Muda; Erlina (Institute of Computer Science (IOCS), 2022)
This study aims to analyze and determine Capital Expenditures, Local Governtment Revenue, Balancing Funds on Per capita Regional Income moderated by Population in the Provinces of North Sumatra, East Kalimantan, and East Java. The population in this study were the provinces of North Sumatra, East Kalimantan, and East Java. And the samples in this study were all districts/cities in the provinces of North Sumatra, East Kalimantan, and East Java. The published data obtained and collected were then analyzed using the Eviews 10 tool. The analytical methods used were descriptive statistics, classical assumption tests, and multiple linear regression for hypothesis testing and moderation testing. Based on the results of data processing using a hypothesis test, it shows that partially Capital Expenditures have a positive and significant effect on Percapita Regional Income, PAD has a positive and significant effect on Per capita Regional Income, the Balancing Fund has an insignificant positive effect on Per capita Regional Income, and through the simultaneous test (F) , overall has a positive and significant effect. And through the moderation test with Population as the Moderating Variable, it shows that the results of Capital Expenditure on Per capita Regional Income can be moderated by Total Population, and Population is able to strengthen the relationship between Capital Expenditures on Per capita Regional Income, PAD on Per capita Regional Income can be moderated by Total Population, and Population is able to strengthen the relationship between PAD and Regional Income Per Capita PAD to Regional Income Per capita NOT able to be moderated by Total Population. The predictive ability of these four variables on Regional Income Per capita is 44.8%, while the remaining 65.2% is influenced by other factors outside this research model.